A Study on the Use of Herbal Medicine for The treatment of HIV/ AIDS: Exploring the Evidence and Safety Concerns of Herbal Medicine for HIV/AIDS Treatment (Journal of Advances and Scholarly Researches in Allied Education, 2017)
In India, herbal medicines are frequently utilized as essential treatment for HIV and for HIV-related issues. By and large, herbal meds are not very much examined, and are ineffectively managed. We audit the confirmation and security concerns identified with the utilization of two particular Indian herbals, which are as of now suggested by the Service of Wellbeing in South India and part states for use in HIV Indian Potato and Sutherland. We survey the pharmacology, toxicology and pharmacokinetics of these herbal medications. Regardless of the fame of their utilization and the help of Services of Wellbeing and NGOs in some Indian nations, no clinical preliminaries of viability exist, and low-level confirmation of mischief recognizes the potential for sedate cooperation’s with antiretroviral medicines. Endeavors ought to be made by standard wellbeing experts to give approved data to herbal healers and patients on the prudent utilization of herbal cures. This may diminish hurt through fizzled desires, pharmacologic antagonistic occasions including conceivable medicationherb communications and pointless included helpful expenses. Endeavors ought to likewise be coordinated at assessing the conceivable advantages of common items in HIV treatment.